Morbidity pattern among tribal farmers in a selected district of Tripura, India - Das, Dipak Kumar; Dhar, Murali (International Journal Of Community Medicine And Public Health, 2024)
Background: Tribal communities in Tripura comprise 31.76% of the state’s total population. The tribal people of Tripura are primarily farmers, and in spite of concerns about their poor health and unfulfilled requirements, they continue to get healthcare in isolated locations where there are obstacles such as undernourishment, a lack of medical facilities, and a labor scarcity. The study’s objective is to ascertain the morbidity pattern among tribal farmers in Tripura. Methods: In 2021 after receiving approval from IIPS, Mumbai, selected farmers from Dhalai district were surveyed. We utilised cross-tabulation, chi2, PCA and straightforward logistic regression. Results: Only 5.17% of the sample population had higher education, 54.1% overall was male, and 23.1% were smokers. Jhum (Hill) cultivation was used by 15.5%, while regular (plain) farming was used by 84.5%. Tribal farmers in Tripura were suffered by both acute and chronic diseases. Diarrhoea and fever amongst acute diseases seemed to have the highest prevalence rates (1.82% each), whereas jaundice and reproductive tract infections have the lowest levels (0.30 each). Asthma had the highest prevalence (3.65%) among the chronic diseases, followed by hypertension (2.74%). The morbidity rate decreased as education levels rose. Normal cultivators and the cultivators who worked more times were more likely to have both acute and chronic diseases than jhum cultivators. Conclusions: It is possible to draw the conclusion that farmers didn’t lead a healthy lifestyle and suffered from diseases. The study’s findings could serve as a foundation for developing economic, educational, and medical plans for tribal farmers to safeguard them from health risks and workplace dangers.